CAE Analysis, Optimization and Fabrication of TU 2014 Formula SAE Vehicle Structure - Kakria, Sahil (My University, 2014)
The objective of the Thesis project is to design & develop FSAE vehicle structure for the year 2014, better than the similar structures designed previously for Thapar University, Patiala as part of Team Fateh for participating in Formula student vehicle design competition held internationally. The focus is to achieve a rigid & lightweight design for TU FSAE 2014 vehicle structure with high stability. The Thesis work started with the study & model building of various subsystems in the TU FSAE vehicle like Double wishbone push rod type Front & Rear Suspension, Rack and pinion type steering system & Space frame type tubular steel chassis. This was followed by analysis & study of the characteristics of the subsystems in the TU FSAE vehicle like roll center for suspension & stiffness/weight for chassis frame. The MBD models of TU FSAE Front & Rear Suspension (2012 & 2014 vehicles) were prepared from the hardpoints extracted from CAD models & were used for carrying out kinematic analysis (suspension wheel travel) to calculate the respective roll centers. The FE models of TU FSAE Chassis (2011, 2012 & 2014) were prepared using Hypermesh by meshing the frames and applying boundary conditions. The models were used for determination of mode shapes, natural frequencies by carrying out normal modes analysis and for calculating chassis stiffness by carrying out linear static analysis. As the Roll center & Torsion stiffness are the two most important quantifiable aspects to the suspension & chassis (respectively) of any race car, their evaluation at subsystem level is essential to analyze the performance of the TU FSAE vehicles. The comparison & improvements in these characteristics of TU FSAE 2014 vehicle over 2011 & 2012 vehicles (all of them being space frame structures) has been presented. Further, the Topology optimization carried out (using input loads from MBD analysis) on various components of TU FSAE 2014 vehicle like Front & Rear suspension Uprights and Chassis Bulkhead and the resultant weight reduction has been described. Finally, the Fabrication of the final design of the frame has been carried out and presented as part of TU FSAE 2014 vehicle structure development.
ME-CAD/CAM-Dissertation
Keywords: Modal analysis; Stiffness analysis; FSAE vehicle; MBD analysis; FEA